Pragmatismo e Semiótica de Peirce na organização da informação - Almeida, Carlos Cândido de [UNESP] (My University, 2010)
Semiotics, as well as its theoretical root, Pragmatism, are associated with the figure of the logical and the American philosopher Charles Sanders Peirce (1839- 1914). Between Pragmatism and Semiotics, there is an embryonic link, and this connection should not be ignored when reflecting on their theoretical contributions the Information Science and, specifically, to knowledge organization. Initially, the relationship between Pragmatism and Semiotics of C. S. Peirce is explored. Subsequently, two contributions of Peirce, both fundamental to understand some aspects of the organization of information and knowledge, are carefully discussed.

La Semiótica, así como su raíz teórica, el Pragmatismo, están asociados a la figura del lógico y filósofo estadounidense Charles Sanders Peirce (1839-1914). Entre Pragmatismo y Semiótica hay un vínculo embrionario, y no se debe descuidar tal conexión cuando se reflexiona sobre las contribuciones teóricas a la Ciencia de la Información, específicamente, a la organización de la información. Se exponen, inicialmente, la relación entre Pragmatismo y Semiótica de C. S. Peirce. Posteriormente, se analizan también dos contribuciones de Peirce, ambas fundamentales para comprender algunos aspectos de la organización de la información y del conocimiento.
Pragmatismo e Semiótica de Peirce na organização da informação
Pragmatism and Semiotics of Peirce in the organization of information
Keywords: Pragmatismo; Semiótica; Organização da Informação e do Conhecimento